2019
DOI: 10.1111/epi.16339
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution mapping of epilepsy prevalence, ambulance use, and socioeconomic deprivation in an urban area of Sweden

Abstract: Objective Geographic differences in epilepsy prevalence between areas of different socioeconomic standing have been demonstrated in the United Kingdom, but knowledge from other health care systems is scarce. Our objective was to compare epilepsy prevalence and emergency medical service (EMS) assignments for seizures in areas of different socioeconomic standings in the urban area of Gothenburg. Methods Register‐based study in Gothenburg (population 690 000), the second largest city in Sweden. Epilepsy cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…In Wales, no evidence of social drift was found by following a cohort of patients with incident epilepsy for 10 years 4 . Taken together, studies to date therefore suggest that social causation, rather than social drift, is the dominant factor contributing to the higher prevalence of epilepsy 1–3 in areas of social deprivation. However, investigation of multigenerational clustering of genes that lower seizure threshold would require prolonged follow‐up, multigenerational family history, and detailed genetic analysis of participants and would be difficult to perform at a population level.…”
Section: Discussionmentioning
confidence: 93%
“…In Wales, no evidence of social drift was found by following a cohort of patients with incident epilepsy for 10 years 4 . Taken together, studies to date therefore suggest that social causation, rather than social drift, is the dominant factor contributing to the higher prevalence of epilepsy 1–3 in areas of social deprivation. However, investigation of multigenerational clustering of genes that lower seizure threshold would require prolonged follow‐up, multigenerational family history, and detailed genetic analysis of participants and would be difficult to perform at a population level.…”
Section: Discussionmentioning
confidence: 93%
“…The possibility that early disadvantage contributed to smaller ICV in Generalized-CI cannot be ruled out. Population-based research has demonstrated higher rates of epilepsy in disadvantaged populations, the disadvantage not due to social drift ( Magnusson and Zelano, 2019 , Pickrell et al, 2015 , Steer et al, 2014 ), and racial and SES factors have been shown to influence features of epilepsy presentation ( Allen et al, 2018 , Allen et al, 2019 ). As disadvantage is known to impact cognition, brain and behavior in the general population, it appears important to more seriously consider these factors in the neuropsychology of epilepsy ( Baxendale and Heaney, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to people from more deprived areas having poorer health literacy and less access to good quality medical care and being encouraged to contact emergency services, particularly out-of-hours ( Peconi et al, 2017 ). Positive correlations have also been shown between deprivation, call rates and population density ( Magnusson & Zelano, 2019 ). This is potentially due to more deprived areas having higher population density and so having more ambulance calls.…”
Section: Discussionmentioning
confidence: 99%